Measurements of inclusive jet spectra in pp and central Pb-Pb collisions at sNN =5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akindinov, A.; et al. (American Physical Society, 2020)
This article reports measurements of the ${p}_{\mathrm{T}}$-differential inclusive jet cross section in $pp$ collisions at $\sqrt{s}=5.02\phantom{\rule{0.16em}{0ex}}\mathrm{TeV}$ and the ${p}_{\mathrm{T}}$-differential inclusive jet yield in $\text{Pb-Pb}$ 0--10% central collisions at $\sqrt{{s}_{NN}}=5.02\phantom{\rule{0.16em}{0ex}}\mathrm{TeV}$. Jets were reconstructed at midrapidity with the ALICE tracking detectors and electromagnetic calorimeter using the anti-${k}_{\mathrm{T}}$ algorithm. For $pp$ collisions, we report jet cross sections for jet resolution parameters $R=0.1--0.6$ over the range $20<{p}_{\mathrm{T},\mathrm{jet}}<140$ $\mathrm{GeV}/c$, as well as the jet cross-section ratios of different $R$ and comparisons to two next-to-leading-order (NLO)--based theoretical predictions. For $\text{Pb-Pb}$ collisions, we report the $R=0.2$ and $R=0.4$ jet spectra for $40<{p}_{\mathrm{T},\mathrm{jet}}<140$ $\mathrm{GeV}/c$ and $60<{p}_{\mathrm{T},\mathrm{jet}}<140$ $\mathrm{GeV}/c$, respectively. The scaled ratio of jet yields observed in $\text{Pb-Pb}$ to $pp$ collisions, ${R}_{\mathrm{AA}}$, is constructed, and exhibits strong jet quenching and a clear ${p}_{\mathrm{T}}$ dependence for $R=0.2$. No significant $R$ dependence of the jet ${R}_{\mathrm{AA}}$ is observed within the uncertainties of the measurement. These results are compared to several theoretical predictions.
Keywords: Physics; Jet (fluid); Spectral line; Jet quenching; Particle physics; Order (exchange); Nuclear physics; Hadron; Quark–gluon plasma; Thermodynamics; https://purl.org/pe-repo/ocde/ford#1.03.03